PERPINDAHAN PANAS PADA AEROPONIK CHAMBER DENGAN APLIKASI ZONE COOLING - Eni sumarni (Jurnal Biofisika, 2013)
Energy  cooling  zone  on  aeroponics  system  for  seed  potato  production  in  the lowland  humid  tropics  can  be  analyzed  based  on  the  principle  of  heat  transfer. Heat transfer  occurring  radiation,  conduction, and convection.  From the calculation of electrical load aeroponics system with cooling zone for seed potato production in lowland  obtained  that the  cooling  zone  temperature of 10°C  requires  the greatest energy. The amount of electrical energy use on a daily average aeroponic chamber amounted to  0.132 kWh/m2 control,  a temperature of 15°C  for  0590  kWh/m2 and a temperature of 20°C for 0439 kWh/m2